Penerapan Sistem Informasi Manajemen Pada Spbu Pertamina Di Dusun Lalawang, Desa Tadui, Kecamatan Mamuju Untuk Meningkatkan Efisiensi Operasional - Aulia Arsil; Jusnaimah; Hari Yeni (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
This study aims to analyze the implementation of Management Information System (MIS) in improving operational efficiency at Pertamina gas stations in Lalawang Hamlet, Tadui Village, Mamuju District. Problems that ofthen arise at traditional gas stations include manual recording of transactions, inaccurate fuel stock control, and delays in operational reporting to management. Thorough field observations, interviews with gas station operators, and documentation reviews. The results show that the use of MIS can speed up the transaction recording process by 40%, increase fuel stock accuracy, and reduce daily recording errors. MIS also helps management in monitoring sales performance in real time. This study concludes that the implementation of MIS plays a significant role in improving the operational efficiency of pertamina gas stations in Lalawang Hamlet.